From Fairy Tale Narratives to Their Animated Versions - Jivanyan, Alvard (Armenian Folia Anglistika, 2006)
The article offers a contrastive study of several classical fairy tales and their animated versions. Animated movies based on fairy tales can be considered the visual version of the tale. Along with a number of similarities, there are also radical differences between the fairy tale narratives and their animated versions. When the fairy tale narrative is converted into a script, along with noticeable plot similarities, a number of essential changes of the linguostylistic and rhetorical features occur. This is conditioned by the character of the cartoon genre. Despite the fact that the poetics of the animated version of a fairy tale is quite flexible, the authors often borrow certain elements of the narrated version which convey the illusion of a text to the animated version.